PERANCANGAN DESAIN UI/UX APLIKASI E-LIBRARY BERBASIS MOBILE MENGGUNAKAN METODE DESIGN THINKING (STUDI KASUS: SMP DAARUN NI’MAH) - Alamry, Syarifah Helmiah; Prihandani, Kamal; Purnamasari, Intan (Jurnal Ilmiah Wahana Pendidikan, 2024)
Data from UNESCO in 2021 revealed that Indonesia's literacy interest ranked 62nd out of 70 countries, becoming a serious concern for the government. Several factors contributed to this worrying trend, including limited access to suitable reading materials and a scarcity of libraries, exacerbated by the impact of the pandemic, which led to a higher focus on digital gadgets. Among students, increased internet usage has resulted in a decline in reading interest due to distractions from social media, digital games, and entertainment content, posing a challenge to improving literacy among students. Additionally, SMP Daarun Ni'mah faces a critical literacy situation with students showing little interest in reading, attributed to inadequate facilities, including the absence of proper reading materials and a library. To address these challenges, this research focuses on designing a user-friendly and appealing user interface (UI) and user experience (UX) for a mobile-based e-library application using the design thinking method. Testing the design using the Single Ease Question (SEQ) and System Usability Scale (SUS) methods with 15 respondents received positive feedback, indicating the effectiveness and acceptance of the UI/UX design. This research aims to promote reading habits and enhance literacy in the digital era through an attractive e-library application.